PEMODELAN DAN SIMULASI KONDENSER ELEKTROHIDRODINAMIK UNTUK SIKLUS KOMPRESI UAP - Rantung, Jotje
Elektrohydrodynamic (EHD) has been applied to generate high electrostatic field over the fluid flow, so tas to destabilize thermal boundary layer which is enhancing the fluid condensation and biling point near the heat transfer space. Numerous eksperimental works using EHD method have been publized. However, none of mathematical modeling and simulation, either steady state or dynamics have been done. In this thesis we modeled and simulated refrigerand condenser based on EHD method, modeling and simulation of EHD condenser will be done. With basis of comparison is experiment result of Da Silva. The simulation result show that heat transfer coefficient folow the trend of Da Silva results. Result show that the highest improvement of heat transfer coefficient able to reach 4,42 times, the highest improvement of heat transfer able to reach 1,66 times, both at voltage 20 kV. Effect EHD enhancement condensation at vapor compression cycle to COP system equal to 8.19.